IDENTIFICATION OF NITROUS OXIDE FOR FORENSIC PURPOSES - Bonchev, Georgi (E-Journal VFU, 2026)
During the last two years the number of reported nitrous oxide (N2O) self-poisoning cases in Northeastern Bulgaria are constantly growing up. Accordingly, there is a substantial increase in demand for analytical toxicology to provide help in fighting the illicit N2O sales and distribution. Although laboratory confirmation of nitrous oxide intoxication in humans is an extremely difficult task, identification of nitrous oxide in physical evidences found at crime scenes proved to be easily achievable. An ultra rapid gas chromatography – mass spectroscopy approach for reliable N2O confirmation, applied for providing irrefutable evidences in crime investigations, is discussed.